The Best American Science writing : 2006 - Gawande, Atul (Ed); Cohen, Jesse (Ed) (New York: Harper Collins Publishers, 2006)
Together these twenty-one articles on a wide range of today's most leading topics in science, from Dennis Overbye, Jonathan Weiner, and Richard Preston, among others, represent the full spectrum of scientific inquiry, proving once again that "good science writing is evidently plentiful" (American Scientist).
ENG
Keywords: Science; Science writings; Technical writing; American essays